Photonic Chip Based on Ultrafast Laser-Induced Reversible Phase Change for Convolutional Neural Network - Jiawang Xie; Jianfeng Yan; Haoze Han; Yuzhi Zhao; Ma Luo; Jiaqun Li; Heng Guo; Ming Qiao (Nano-Micro Letters)
Highlights Programmable photonic chips based on ultrafast laser-induced phase change is fabricated for photonic computing. Based on the integrated photonic chip, photonic convolutional neural networks are built to implement machine learning algorithm, and images recognition task is achieved. The transient laser-induced phase change dynamics of Sb film are revealed at atomic scale, and the phase change time is measured.